PRAKTIK EGALITARIAN DI PANGGUNG MTQ INDONESIA: TELAAH PEMIKIRAN ANNE K. RASMUSSEN - Lukita, Jimmy; Rohmaniyah, Inayah (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
The role of women as Qur'an readers in the public sphere is still considered taboo in many Islamic countries, especially those in the Middle East. This condition is different for Anne K. Rasmussen, where women can freely perform their reading of the Qur'an at MTQ activities held in Indonesia. Not only in terms of reciting the Qur'an, the egalitarian practice that developed in MTQ activities was also in the form of women as judges and audiences at every performance of the Qur'an recitation. In his book, Rasmussen mentions at least three factors that trigger the occurrence of egalitarian practices in this MTQ activity, 1) educational-religious factors, 2) socio-cultural factors, 3) political policy factors. This research was conducted using an analytical descriptive method and a qualitative approach, with which this article tries to reveal Rasmussen's thoughts that explain that in MTQ activities there are egalitarian practices, there are background factors, and have implications for the activity itself. Among the implications are knowledge implications, norm implications, and practice implications.